Advocacy and Capacity Building in Open Access (OA) and Open Science (OS) to top management staff in African Higher Education Institutions, in Egypt - El-Shari, Amany; Bahei-El-Din, Yehia; Corletey, Abednego; Persic, Ana; Anand, Roheena; Wanyenze, Rhoda; El-Hefnawy, Aly; Mchunu, Nokuthula P.; Rafols, Ismael; Owango, Joy (My University, 2022)
This was the second of a series of workshops on Advocacy and Capacity Building in Open Access & Open Science to top management staff in African Higher Education Institutions by the AAU and supporting partners PLOS and TCC Africa. It was hosted by the British University in Egypt.
Day 1 Recording https://africarxiv.pubpub.org/pub/41o17vxi#day-1-recording Day 2 Recording https://africarxiv.pubpub.org/pub/41o17vxi#day-2-recording
Keywords: Open Access; Open Science; Egypt